Aura Farming: Fenomena Viral Tradisi Pacu Jalur sebagai Strategi Jenama dalam Pengembangan Pariwisata Budaya di Riau - Aisyah Astinadia Siregar (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2026)
This study examines the viral phenomenon known as “Aura Farming” within the traditional Pacu Jalur boat race in Riau, Indonesia, and its significance as a strategic branding approach for cultural tourism development. Pacu Jalur, a centuries-old rowing competition, has recently gained widespread attention on digital platforms, leading to an increase in tourism interest and cultural visibility. Employing a qualitative case study methodology, the research incorporates in-depth interviews with local stakeholders, participatory observation during festival events, and content analysis of social media to explore how Aura Farming amplifies the tradition’s appeal. The findings indicate that this viral phenomenon not only strengthens the cultural identity and pride of the local community but also plays a vital role in enhancing the region’s tourism branding efforts by attracting diverse tourist segments. Furthermore, the study underscores the importance of leveraging digital media and user-generated content to promote intangible cultural heritage effectively, suggesting that integrating traditional cultural events with modern branding strategies can increase regional competitiveness in the global tourism market. This paper offers practical implications for policymakers, tourism managers, and cultural practitioners seeking to balance cultural preservation with tourism development in a digital age.